2001
DOI: 10.1021/ma0106649
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular-Structured Hydrogels Showing a Reversible Phase Transition by Inclusion Complexation between Poly(ethylene glycol) Grafted Dextran and α-Cyclodextrin

Abstract: Supramolecular-structured hydrogels were prepared on basis of the inclusion complexation between poly(ethylene glycol) grafted dextrans and R-cyclodextrins (R-CDs) in aqueous media. The inclusion complexes from the PEG grafted dextrans showed a unique gel-sol phase transition which cannot be obtained from usual polymer inclusion complexes that form crystalline precipitates. The gelsol transition was based on the supramolecular assembly and dissociation, and the transition was reversible with hysteresis. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
190
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 26 publications
10
190
0
1
Order By: Relevance
“…In addition, with the exception of conjugation sites, no changes in the other sites of polysaccharides are preferred. Several methods had been reported to PEGylate neutral polysaccharides like dextran [20][21][22][23] and inulin. 24,25 Among these methods, the one used in the study, which utilizes a moderate coupling reaction between the hydroxyl-activated polysaccharide and the amino-terminated mPEG, was believed to be more suitable for PEGylation of polysaccharide-based drugs than those that cause charged conjugates 21 or require highly alkaline conditions for the coupling, 23 since it allows the unreacted activated hydroxyls of polysaccharide to return to their original form easily by hydrolysis in a weakly alkaline solution and thus ensures the least influence on the polysaccharide structure and, in turn, on bioactivity.…”
Section: Preparation Of Pegylated Ropsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with the exception of conjugation sites, no changes in the other sites of polysaccharides are preferred. Several methods had been reported to PEGylate neutral polysaccharides like dextran [20][21][22][23] and inulin. 24,25 Among these methods, the one used in the study, which utilizes a moderate coupling reaction between the hydroxyl-activated polysaccharide and the amino-terminated mPEG, was believed to be more suitable for PEGylation of polysaccharide-based drugs than those that cause charged conjugates 21 or require highly alkaline conditions for the coupling, 23 since it allows the unreacted activated hydroxyls of polysaccharide to return to their original form easily by hydrolysis in a weakly alkaline solution and thus ensures the least influence on the polysaccharide structure and, in turn, on bioactivity.…”
Section: Preparation Of Pegylated Ropsmentioning
confidence: 99%
“…To date, nuclear magnetic resonance (NMR) and gel permeation chromatography (or size-exclusion chromatography) are the most commonly used methods to characterize PEGylated polysaccharides. Since ROP is a fructan and thus lacks an anomeric proton, the 1 H NMR method used to determine the grafting degree of PEGylated dextrans 20 was found to be inapplicable for PEGylated ROPs. It was also found that the confirmation of PEGylation by 1 H NMR or Fourier transform infrared spectroscopy was impractical due to the very few carbamate bonds in the conjugates prepared.…”
Section: Characterization Of Conjugates and Fitc-labeled Conjugatesmentioning
confidence: 99%
“…In the recent years, polymer inclusion complexes with cyclodextrins have received much attention due to some properties such as crystallization performance, 1 degradation, 2 thermal-stability property 3 and have exhibited potential applications in bio-pharmaceutical industry such as tissue engineering, 4 drug controlled release carrier, 5 and functional polymer based composite materials. 6 Cyclodextrins are a series of cyclic oligosaccharides containing 6, 7, or 8 D (+)-glucose unites linked by α-1, 4-linkages, namely α-, β-, and γ-CD respectively.…”
Section: Introductionmentioning
confidence: 99%
“…CD molecule possesses a unique structure like truncated cone including hydrophilic outer surface and hydrophobic cavity with the capacity to accommodate different guest molecules. [1][2][3]5,6 In aqueous solution, the slightly apolar CD cavity is occupied by energetically unfavored water moleculars which are easily replaced by appropriate guest molecules with less polar. 7 The guests may be hydrophilic or hydrophobic small molecules and polymer macromolecules, which can form inclusion complexes with cyclodextrins.…”
Section: Introductionmentioning
confidence: 99%
“…Various supramolecular hydrogels have been developed and investigated as drug delivery systems. Some examples include blending linear polymers such as poly(ethylene oxide) (12); grafting copolymers composed of dextran as a backbone and poly(ethylene glycol) (PEG) as a linear side chain (13);and di-/tri-block copolymers consisting of poly caprolactone and PEG with α-CD (7,14,15).…”
Section: Introductionmentioning
confidence: 99%